KARAKTERISTIK KIMIA DAN AKTIVITAS ANTIOKSIDAN SELAI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) DENGAN PENAMBAHAN BUNGA ROSELLA (Hibiscus sabdariffa. L) DAN KONSENTRASI SUKROSA - Wijantri Kusumadati; Suparno Suparno; Muliansyah Muliansyah; Nisa’i Khoiriyah (Politeknik Pertanian Negeri Samarinda, 2023)
Red dragon fruit peels and rosella flower petals are combined with a concentrated sucrose to be processed into jam which has health benefits. These benefits are obtained from the antioxidant content of of both ingredients thatcan prevent degenerative diseases. The purpose of this study was to determine the effect of adding rosella flower extract and the appropriate concentration of sucrose on the chemical, organoleptic , and antioxidant activity of good red dragon fruit peel jam. Based on the test results, the jam with the best quality will also be determined. The experimental design used a factorial completely randomized design with three treatments of rosella flowers; 20, 30, and 40% and the sucrose concentrations were 50, 60 and 70%, and repeated three times. The results showed that the combination of rosella calyx and sucrose jam had an effect on pH, vitamin C, antioxidant activity, color, texture and aroma but had no significant effect on water content, total dissolved solids, reducing sugar and taste. Jam treatment with a concentration of 70% sucrose and 30% rosella flower extract produced the best quality based on chemical, physical and organoleptic parameters.